1977
DOI: 10.1177/00220345770560071901
|View full text |Cite
|
Sign up to set email alerts
|

An Autoradiographic Study of the Sensory Innervation of Teeth. I. Dentin

Abstract: Autoradiography of axoplasmically transported proteins revealed that the coronal dentin of rat molar teeth receives sensory innervation from the trigeminal ganglion. The labeled processes appear to run in dentinal tubules and sometimes reach the peripheral dentinal region near the enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This restriction to the inner regions is in general agreement with the findings of Fearnhead (19571, who describes axons at a maximum distance of 0.4 mm beyond the predentin and with the autoradiographic results of Byers (1977). Two other autoradiographic tracer studies in the rat (Quinton-Cox, 1975;Pimendis and Hinds, 1977) describe labeled material in the outer dentin near to enamel-dentin junction. In this and earlier studies (Brannstrom and Garberoglio, 1974;Holland, 1976c) no cell processes have been seen in this region.…”
Section: Discussionmentioning
confidence: 99%
“…This restriction to the inner regions is in general agreement with the findings of Fearnhead (19571, who describes axons at a maximum distance of 0.4 mm beyond the predentin and with the autoradiographic results of Byers (1977). Two other autoradiographic tracer studies in the rat (Quinton-Cox, 1975;Pimendis and Hinds, 1977) describe labeled material in the outer dentin near to enamel-dentin junction. In this and earlier studies (Brannstrom and Garberoglio, 1974;Holland, 1976c) no cell processes have been seen in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Their central processes pass to the Main Sensory Trigeminal Nucleus (MSTN) while others pass to the Spinal Tract of the Trigeminal Nucleus (STTN). Autoradiographic studies have shown that the afferent nerves from periodontal receptors end in the Gasserian ganglion (Pimenidis & Hinds 1977, Byers & Holland 1977). It appears from the first study, that by labeling the cells in the Gasserian ganglion with tritiated L-Proline, the periodontal ligament is only moderately labelled, while the labeling of the free gingiva is prominent.…”
Section: Central Connectionsmentioning
confidence: 99%
“…So far, autoradiography of rat molars (Fink et al, 1975;Byers and Kish, 1976;Pimenidis and Hinds, 1977;Byers, 1977Byers, , 1979Byers, , 1980Byers et al, 1982b) and of cat teeth (Byers and Matthews, 1981) has shown that dentin is innervated, that nerve endings are most numerous in the tubular dentin near the tip of the pulp horn, that some nerve endings can be found in radicular dentin, and that a few axons cross the midline in cats to innervate contralateral incisors (for review, Byers, 1983).…”
mentioning
confidence: 99%